2010
DOI: 10.1016/j.jpowsour.2009.09.072
|View full text |Cite
|
Sign up to set email alerts
|

High capacitance B/C/N composites for capacitor electrodes synthesized by a simple method

Abstract: The B/C/N composites were synthesized by a very simple method, that is, carbonization at HTT = 800-1200˚C of the precursor prepared by drying a solution mixture of polyacrylamide and boric acid, followed by boiling in water to remove borate by-products. The amount of insoluble B species in the composite increased linearly from 4.8 to 18.6 mass% with raising HTT. The XRD and FT-IR , larger for lower HTT, in the acid and neutral electrolytes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 27 publications
(41 reference statements)
0
56
0
Order By: Relevance
“…Recently, boron and nitrogen co-doped carbon materials were reported for electrochemical capacitors [145,146]. The co-doped porous carbons were derived from gels which were prepared from citric acid, H 3 BO 3 and NH 4 OH using NiCl 2 as an activating agent [145].…”
Section: Sample Code Precursor Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, boron and nitrogen co-doped carbon materials were reported for electrochemical capacitors [145,146]. The co-doped porous carbons were derived from gels which were prepared from citric acid, H 3 BO 3 and NH 4 OH using NiCl 2 as an activating agent [145].…”
Section: Sample Code Precursor Preparationmentioning
confidence: 99%
“…Any correlation between capacitance and composition was absent, and the effect of boron and nitrogen was not discussed in detail. More simple method to form the co-doped carbons was reported, that is, carbonization of the precursor prepared by drying a solution mixture of polyacrylamide (PAA) and H 3 BO 3 , followed by boiling in water to remove borate by-products [146]. The boron content increased linearly from 4.8 to 18.6 mass% in a range of carbonization temperature of 800-1200 • C, in parallel with the change in the relative intensity of B 1 s peak to C 1 s peak by XPS.…”
Section: Sample Code Precursor Preparationmentioning
confidence: 99%
“…Despite specific capacitances are lower than that of conducting polymers or metal oxides, porous carbons triumph over their competitors in commercial devices because of their greater cycle stability and higher electrical conductivity [3e6]. Substitution of carbon atoms with heteroatoms (such as nitrogen [8], boron [9], phosphorus [10], and oxygen [11]) in the basal planes and/or at the edges endows them with exciting properties due to the tailored electronic structure and surface properties. Therefore, heteroatomdoped carbons have recently drawn much attention because of their potential applications in metal free heterogeneous catalysis, solar energy conversion, lithium ion batteries, and fuel cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Though these reactions are not visible in our studies with JFSC at the scan rate investigated the above reasons may still be valid to explain the capacitance obtained. Few studies on the electrode cell performance of activated carbons in Na 2 SO 4 show that the pseudo-Faradaic redox transitions of O and N-containing electroactive surface groups are depressed in this electrolyte in comparison with H 2 SO 4 [36,70,[81][82][83] . Nevertheless, Andreas and Conway [77] have indicated that the pseudo-capacitive contribution of surface oxygenated groups is negligible at neutral pH but Bichat et al [71] have affirmed that pseudo-Faradaic reactions with seaweed derived carbon are possible in 0.5M Na 2 SO 4 with adequate surface functionalities on the carbon surface.…”
Section: Discharge Cycling Studiesmentioning
confidence: 97%